2018
DOI: 10.1152/ajpregu.00402.2017
|View full text |Cite
|
Sign up to set email alerts
|

Social status affects lipid metabolism in rainbow trout,Oncorhynchus mykiss

Abstract: Juvenile rainbow trout ( Oncorhynchus mykiss) confined in pairs form social hierarchies in which socially subordinate fish display characteristic traits, including reduced growth rates and altered glucose metabolism. These effects are, in part, mediated by chronically elevated cortisol levels and/or reduced feeding. To determine the effects of social status on lipid metabolism, trout were held in pairs for 4 days, following which organismal and liver-specific indexes of lipid metabolism were measured. At the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 90 publications
(154 reference statements)
4
34
0
Order By: Relevance
“…Standard curves and noRT controls were used to assess efficiency and specificity of amplifications as previously described. The ΔΔCT method for normalization [70] was adopted using snoU23 as a reference gene, as previously described for rainbow trout [77]. The miRNA fold changes were then calculated relative to each CTL group (5 or 9 months old, in each case), as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Standard curves and noRT controls were used to assess efficiency and specificity of amplifications as previously described. The ΔΔCT method for normalization [70] was adopted using snoU23 as a reference gene, as previously described for rainbow trout [77]. The miRNA fold changes were then calculated relative to each CTL group (5 or 9 months old, in each case), as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Socially dominant (SD) fish within these hierarchies monopolize preferred territories, displaying high levels of aggression towards their socially subordinate (SS) counterparts [1,3]. These differences in behaviour are accompanied by a range of physiological responses, including changes in energy metabolism [47]. Previous studies revealed an increased potential for hepatic glucose liberation in SS compared to SD fish.…”
Section: Introductionmentioning
confidence: 99%
“…However, although circulating glucose represents an important fuel source for specific rainbow trout tissues, such as the brain [11], glucose utilization for global energy metabolism in most other tissues is limited in rainbow trout [12]. In contrast, lipid metabolism is a key player in global energy metabolism in trout [7], and SS trout exhibit increased reliance on free fatty acids, as indicated by elevated circulating free fatty acid concentrations at the organismal level, and by increased expression of the mitochondrial free fatty acid transporter carnitine palmitoyltransferase ( cpt1a ) which is rate limiting to mitochondrial β-oxidation [7]. Conversely, SD trout reveal increased capacity for hepatic de novo lipogenesis, as indicated by increased abundance of the transcription factor sterol regulatory element binding protein 1c ( srebp1c ) and the enzyme fatty acid synthase ( fasn) mRNA, which coincide with increased circulating levels of triglycerides [7].…”
Section: Introductionmentioning
confidence: 99%
“…Periods of ascension are often associated with elevated glucocorticoid production (Huffman et al 2015;Culbert et al 2018), and the catabolic actions of glucocorticoids likely aid in the rapid mobilization of these energy reserves (Mommsen et al 1999). In rainbow trout (Oncorhynchus mykiss), social subordination is associated with elevated cortisol production, which, at least in part, results in increased rates of hepatic gluconeogenesis (Gilmour et al 2012) and betaoxidation (Kostyniuk et al 2018), along with depletion of energy reserves, including liver glycogen (Gilmour et al 2012;Culbert and Gilmour 2016). A similar process may occur during ascension, where increased cortisol production (Culbert et al 2018) stimulates the mobilization of energy reserves, providing ascenders with the fuel necessary to establish dominance.…”
Section: Discussionmentioning
confidence: 99%